A DFT based assay for tailor-made terpyridine ligand–metal complexation properties. Issue 8 (23rd May 2016) - Joshi, Krati; Krishnamurty, Sailaja; Singh, Iksha; Selvaraj, Kaliaperumal
Abstract : Electron-rich terpyridine ligand and its metal complexes have a potential to grow as responsive surfaces by adapting their physicochemical properties as a function of environment. The responsiveness is brought about by judicious molecular level designing that is currently hindered due to lack of information and control on terpyridine (TPy)–metal (M) interactions at single molecule level. So far there is no organised understanding on the binding of different metals with TPy ligand and ways to modulate it. Being a large conjugated system, TPy has a large scope to be functionalised with electron exchanging groups to alter its electronic structure and consequently its binding with metal atoms. In first report of such a kind, using density functional theory (DFT), we demonstrate that convenient modulation of TPy-M binding is possible through functionalisation of TPy for, Ru, Fe, Mo and Au. Electron donating groups viz., CH, OCH, C H, NH and electron withdrawing groups viz., CF, COOH, CN and NO are considered for functionalisation of TPy ligand. Significantly, the present work focuses on the functionalisation at 4 and 4 positions of TPy molecule. The role of such a functionalisation in influencing the ligands structure–property correlation is missing in the literature to the best of our knowledge. The present investigation quantifies that by pertinent functionalisation of TPy, TPy-M binding energies can be modified up to 60 kcal/mol. Our results reveal that functionalisation leads to a considerable charge redistribution within the TPy-M complex with carbon atoms in pyridine rings functioning as major electron sink/source with a corresponding red/blue shift of stretching frequency. This modifies the red-ox, optical and other chemical properties of TPy-M complexes. In brief, the present report illustrates a way to design ligands such as TPy for diverse applications through tailor-made functionalisation using electronic structure methodology.